The Introduction of Anthropometrics into Development and Labor Economics - John Komlos; Lukas Meermann (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
We trace the introduction of anthropometric indicators into development and labor economics in the late 1970s.
urn:nbn:de:bvb:19-epub-381-8
Keywords: B20; B40; N01; 330; Anthropometrics; development economics; labor economics; history of economic thought